2016 International Conference on Electrical, Electronics, and Optimization Techniques (ICEEOT) 2016
DOI: 10.1109/iceeot.2016.7755147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometric parameters on the acoustical performance of single inlet single outlet expansion chamber muffler

Abstract: Muffler is an important component in any machinery where sound is needed to be muffled or attenuated. Mufflers of various geometric configurations are available with main focus on getting maximum transmission loss without having undesirable impact on back pressure. This paper predicts the acoustical performance of a single inlet single outlet expansion chamber muffler. Finite element method is used to predict the transmission loss of the muffler at different geometrical parameters and then these results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The three-point method is also the fastest method and is easy to use; whereas, the quadruple method is not so straightforward to deal with (Bilawchuk, Fyfe, 2003;Dube et al, 2018). The acoustic performance of the expansion chamber depends on the cross-sectional area; so that, the transmission loss parameter decreases if the diameter of the expansion chamber increases (Cao et al, 2017;Łapka, 2014;Nag et al, 2017;Zhang et al, 2009). In the low-frequency range, the transmission loss values are equal to the results obtained from the plane wave theory.…”
Section: Introductionmentioning
confidence: 86%
“…The three-point method is also the fastest method and is easy to use; whereas, the quadruple method is not so straightforward to deal with (Bilawchuk, Fyfe, 2003;Dube et al, 2018). The acoustic performance of the expansion chamber depends on the cross-sectional area; so that, the transmission loss parameter decreases if the diameter of the expansion chamber increases (Cao et al, 2017;Łapka, 2014;Nag et al, 2017;Zhang et al, 2009). In the low-frequency range, the transmission loss values are equal to the results obtained from the plane wave theory.…”
Section: Introductionmentioning
confidence: 86%
“…The perforated pipe strongly affects the attenuation performance of the resonator [23]. Limited by finite volume for the engine nacelle and maintaining constant external muffler dimension requires little or no change in the length of the chambers [24][25]. The perforated and insertion pipes are the main muffler units that affect muffler performances.…”
Section: B Orthogonal Test Designmentioning
confidence: 99%
“…where W i and W o are inlet and outlet power, respectively. The TL is calculated in each step of the muffler design including any physical change in the proposed muffler that affected the acoustical performance of the mufflers [14][15][16][17][18]. There is wide research discussing these parameters and investigating muffler performance by TL.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in that study that the overall TL of the cylindrical muffler would increase with the increment of the absorptive layer [15]. In another study, Nag et al (2016) analyzed the diameter for a single inlet single outlet expansion chamber and showed that increasing diameter caused improvement in TL [16]. Further, Amuaku et al (2019) focused on chamber perforations and inlet and outlet diameter variations on TL for an elliptical shape muffler and conclude that perforation has a more significant impact on performance [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation